Reproduction performance parameters in Iberian pig farms - Piñeiro C.; Aparicio M.; De Andrés M.A.; Rainho N.; Rodríguez-Estévez V. (7th International Symposium on the Mediterranean Pig, 2012)
Technical efficiency of the production is very important for cost control. As an industry, swine producers need to collect production data to use these to make decisions on their farms. Producers need benchmarks to compare their farm performances. There are few reproduction performance parameters about Iberian pigs. A total of 8 farms and 3400 sows providing data in a routine have been included in this first study summarizing 2009 results. Data were imported from different software brands, uniformized and merged in a single data base, from which the analysis was performed using Pigchamp© software, obtaining the following mean values: weaning to service interval = 8,4 days, farrowing rate = 75 %, returns to estrus = 18,4 %, total born = 8,3, born alive = 7,8, weaned piglets = 7, number of litters per sow and year = 2,11, piglets weaned per sow and year = 14,4. The aim of this paper is to provide a first structured batch of the most important reproductive parameters.
7. International Symposium on the Mediterranean Pig, 2010/10/14-16, Córdoba (Spain)